Alteration of Thyroid Hormone Pictures in Absence of Clinically Evident Thyroid Diseases among Type2 Diabetic Subjects in a Bangladeshi Population (Global Journal of Medical Research, 2021)
Abstract not found
Keywords: euthyroid sick syndrome (ESS); diabetes mellitus; body mass index (BMI)